Evaluating the state’s response to flooding disasters: the case of deelpan village emergency housing - Rirhandzu, Chuma (University of the Witwatersrand, Johannesburg, 2024)
Over the past few years, South Africa has been struggling with managing flooding episodes. From a housing point of view, one then worries about the living conditions of the poor people who do not have the necessary resources to recover from the effects of the disaster, like the people of Deelpan Village in the North West province. To obtain data for this research, I analysed secondary data in relation to disaster management, housing, and planning accessed from government websites. I also conducted a total of 18 semi-structured interviews with the officials and community representatives who were actively involved in the Deelpan Village emergency housing project. This study revealed that the people of Deelpan preferred permanent housing structures over temporary solutions; hence, the Temporary Residential Units have not been provided. The study concluded that the Deelpan residents rejected TRUs for permanent structures due to fear of state failure. Three years after the 2021 flooding, no housing support has been provided by the state, indicating a lack of resources to handle disasters.
A research report submitted in fulfillment of the requirements for the asters of Urban Studies (Housing and Human Settlements), In the Faculty of Engineering and the Built Environment , School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Flooding disaster; Deelpan village; State; SDG-15: Life on land